The Tasaday stone age people in a space age world - The Associated Press; The Center for Humanities Guidance Associates; Pathescope Educational Media (Mount Kisko, N.Y. The Center [producer], 1987)
A coverage of a group of people discovered in the Philippines in 1971. It shows their stone age way of life and trace the effects of modern civilization on their culture.
VHS.
Keywords: Tasadays